Rancang Bangun Sistem Informasi Asistensi Berbasis Website Menggunakan Teknologi MERN Stack - Ahmad Khainur Nadhif; Lilik Sugiarto; Sri Widyanti (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
The STMIK Amikom Surakarta Assistant Forum is a forum under the UPT STMIK Amikom Surakarta which aims to assist the system of teaching and learning activities in STMIK Amikom Surakarta lectures. In the process of assistance activities taking place, assistants have several problems such as filling out attendance papers that use paper as evidence for attendance that has carried out assistance tasks, then in the process of recapitulating the treasurer's attendance as financial administrators must collect proof papers on each assistant making less effective, and lastly during the scheduling process that uses Excel as a scheduler tool, and will later be shared through groups, this creates a lack of schedule synchronization if at any time there is an updated schedule. Because of this problem the author aims to solve these problems by creating an information system that can perform attendance, recapitulation, and scheduling without using paper and efficiently. The researcher in this research process uses the RAD (Rapid Application Development) method because this method is fast and efficient in the development process. In the manufacturing process, researchers use MERN Stack technology.